STRENGTHENING PANCASILA MORAL VALUES THROUGH RELIGIOUS EXTRACURRICULAR ACTIVITIES AT SMPN 4 GARUT - Fuzi Astuti Rahayu; Arik Darojat; Supriadi (SAHUR Journal, 2026)
The instillation and strengthening of Pancasila moral values is a strategic effort to shape a young generation who are noble, tolerant, and have a strong national spirit. This study aims to describe how religious extracurricular activities contribute to strengthening students’ Pancasila moral values at SMPN 4 Garut. The research employed a qualitative method with a descriptive-analytic approach. Data were collected through observation, in-depth interviews with PPKn teachers in grades VII and IX as well as supervisors of religious extracurricular activities, and documentation of school programs. Data analysis followed the stages of data collection, data reduction, data presentation, and drawing conclusions, while the credibility of the findings was tested through source triangulation. The results show that religious extracurricular activities such as Duha prayer, reading morning dhikr, reciting short surahs and Asma’ul Husna, Friday prayer, Islamic holy day celebrations (PHBI), girl-focused keputrian activities, “embun pagi”, and Friday charity have been consistently implemented. These activities help nurture Pancasila moral values including honesty, responsibility, empathy, mutual respect, independence, discipline, and social care in students’ daily behaviour. However, the implementation still faces several obstacles, such as limited cooperation among teachers in guiding students and the low awareness of some students who are difficult to direct toward positive behaviour. Overall, religious extracurricular activities at SMPN 4 Garut play an important role in strengthening students’ Pancasila moral values and need to be continuously optimized through better coordination and support from all school stakeholders. Keywords: Pancasila moral values, Reinforcement, Religious extracurricular activities.